KHALWAH; ANALYTICAL STUDY OF PROPHET MUHAMMAD'S TRADITION - Ummi Farqah (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2020)
The purpose of this study is to understand the interpretation of the ahadith on the prohibition of khalwah. Nowadays, we are facing there are many people do not follow the limitation prescribed by shari’ah during their engagement period and they are still involving in khalwah in the Muslim world. This happens mainly because majority of those are not aware of the ahadith on prohibition of khalwah or they do not have better understanding of the ahadith. Thus, this study to analyze ahadith of the khalwah. The conclusion reached for this research shows that all interpretation of the ahadith agreed on the prohibition of khalwah. Finally, the result indicates that the understanding towards the ahadith on the prohibition of khalwah should be strongly instilled in every moslem. Thus, they will leave khalwah even they are engaged.